MEDICATION REVIEW OF CHILDREN ON LONG TERM MEDICATIONS: A REVIEW OF THE LITERATURE. Issue 9 (17th August 2016) - Aston, Jeff; Huynh, Chi; Sinclair, Anthony; Wilson, Keith; Terry, David
Abstract : Introduction: Children on long term medication may be under the care of more than one medical team including the patients GP. Children on chronic medication should be supported and their medications reviewed, especially in cases of polypharmacy. Medicines Use Reviews (MURs) were introduced into the pharmacy contract in 2005. The service was designed for community pharmacists to review patients on long term medication. The service specified that MURs were done on patients who can give consent and cannot be conducted with a parent or carer. Hence the service may be inaccessible to paediatric patients. This review aims to find studies that identify medication review services in primary care that cater for children on long term medication. Methods: A literature search was conducted on 6th June 2015 using the keywords, ("Medication" or "review" or "Medication Review" or "Medicines use review" or "Medication use review" or "New Medicine Service") AND ("community pharmacy" OR "community pharmacist" OR "primary care" OR "General practice" OR "GP" OR "community paediatrician" OR "community pediatrician" OR "community nurse"). Bibliographic databases used were AMED, British Nursing Index, CINAHL, EMBASE, HMIC, MEDLINE, PsycINFO and Health Business Elite. Inclusion criteria were: paediatric specific medication review in primary care, for example by either a GP, community paediatrician, community nurse or community pharmacist. Exclusion criteria were studies of medication review in adults/unclear patient age and secondary care medication reviews. Results: From the 417 articles, 6 relevant articles were found after abstract and full text review. 235 articles were excluded after title and abstract review (11 did not have full text in English); 96 were adult or non-age specified medication review/MUR/New Medicine Service studies; 63 referred to observational, evaluative studies of interventions in adults; 6 were non-paediatric specific systematic reviews and 17 were protocols, commentaries, news, and letters. The 6 relevant articles consisted of 1 literature review (published 2004), 3 research articles and 1 published protocol. The literature review[1] recommended that children's long term medication should be reviewed. The published protocol stated that the NMS minimum age for inclusion in the trial was for children aged over 13 years of age. The four studies were related to psychiatrists reviewing paediatric mental health patients in the USA, a pharmacist using Drug Related Problem to review patients in GP practices in Australia, a UK study based on an information prescription concept by providing children dispensed medications in community pharmacy with signposting them to health information and one GP practice based study observing pharmaceutical care issues in children and adults. Conclusion: The results show that there are currently no known studies on medication use reviews specific to children, whereas in adults, published evaluations are available. The terms of the MUR policy restrict children's access to the service and so more studies are necessary to determine whether children could benefit from such access.